2016
DOI: 10.1016/j.neulet.2016.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Tsc1 haploinsufficiency is sufficient to increase dendritic patterning and Filamin A levels

Abstract: Most individuals with tuberous sclerosis complex (TSC) are born with a mutant allele of either TSC1 or TSC2 and a mosaic of psychological and cognitive defects. Tsc1 loss of heterozygosity contributes to severe dendritic abnormalities that are rescued by normalizing the levels of the actin-cross linking protein, Filamin A (FLNA). However, it is unclear whether dendrites and FLNA levels are abnormal in an heterozygote Tsc1 condition. Here, we examined dendritic morphology and FLNA levels in the olfactory bulb o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Indeed, expressing the gain-of-function mTOR variants, mTOR L1460P and S2215Y, in cortical neurons in vitro did not lead to an increase in FLNA level (Zhang et al, 2020). Dysregulation of MAPK/ERK signaling and increased FLNA levels have also been reported in conditional Tsc1 −/− and Tsc1 ± mice (Zhang et al, 2014(Zhang et al, , 2016. Thus, altered MAPK/ERK-FLNA function represents an mTORC1-independent mechanism that contributes to cortical malformations and epilepsy in TSCand RHEB-related mTORopathies.…”
Section: Differential Activation Of Intracellular Pathways In Mtoropathiesmentioning
confidence: 93%
“…Indeed, expressing the gain-of-function mTOR variants, mTOR L1460P and S2215Y, in cortical neurons in vitro did not lead to an increase in FLNA level (Zhang et al, 2020). Dysregulation of MAPK/ERK signaling and increased FLNA levels have also been reported in conditional Tsc1 −/− and Tsc1 ± mice (Zhang et al, 2014(Zhang et al, , 2016. Thus, altered MAPK/ERK-FLNA function represents an mTORC1-independent mechanism that contributes to cortical malformations and epilepsy in TSCand RHEB-related mTORopathies.…”
Section: Differential Activation Of Intracellular Pathways In Mtoropathiesmentioning
confidence: 93%
“…Finally, it is worth mentioning that in addition to tumor formation and patient variability in tumor spectrum, TSC patients may present a variety of non-tumoral symptoms, including seizures and complications in the central nervous system. Zhang et al (2016) found that Tsc1 haploinsufficiency is associated with increased dendritic complexity and total dendritic length as well as increased Filamin A levels in the olfactory bulb of Tsc1 heterozygote mice. This could contribute to a spectrum of cognitive or psychiatric disorders in TSC patients (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Zhang et al (2016) found that Tsc1 haploinsufficiency is associated with increased dendritic complexity and total dendritic length as well as increased Filamin A levels in the olfactory bulb of Tsc1 heterozygote mice. This could contribute to a spectrum of cognitive or psychiatric disorders in TSC patients (Zhang et al, 2016). Recently, Haji and colleagues investigated the consequences of heterozygous knockout of Tsc1 in hippocampal medial ganglionic eminence cells and found impairment in their spatial working memory and a decrease in synaptic inhibition of pyramidal cells.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have shown that mTORC1 activation increases dendritic complexity in olfactory granule neurons. Postnatal deletion of TSC1 drives dendritic hypertrophy in granule neurons [ 110 , 117 ]. Moreover, Rheb activation increases dendritic branching of granule neurons, particularly basal dendrites [ 111 , 118 ].…”
Section: Role Of Mtorc1 In Neurite Development and Synapse Formatimentioning
confidence: 99%